Fiscal transparency and public service quality association: Evidence from 12 coastal provinces and cities of China - Qiuxia Yang (Journal of Risk and Financial Management, 2021)
This paper presents an evaluation index system of public service quality, which contains 35 indexes from the dimensions of the output and effect. Based on data from 2010 to 2017 in 12 coastal provinces and cities of China, this paper assesses public service quality by using the methods of entropy weight order preference similarity to the ideal solution (TOPSIS) and analyzes the effect of fiscal transparency on public service quality. The results show that the public service quality in the 12 coastal provinces and cities of China studied is relatively high, and fiscal transparency has a positive effect on public service quality. This analysis showed that an increase of 1% in fiscal transparency would lead to an increase of 0.0323% in the quality of public services. Fiscal transparency contributes to the quality of public services by improving the scale of investment and the efficiency of public services expenditure; this is because fiscal transparency can increase the expenditure on public welfare services and curb official corruption. Furthermore, the proposed evaluation index can enable government administrators to take the necessary steps on the appropriate dimensions to improve public service quality. This study can provide some guidelines for other countries, especially to improve public service quality by increasing fiscal transparency.
Keywords: 330; fiscal transparency; public policy; public service quality; TOPSIS